A systematic review and meta-analyses of sentinel lymph node identification in breast cancer and melanoma, a plea for tracer mapping. Issue 4 (April 2016) - Niebling, M.G.; Pleijhuis, R.G.; Bastiaannet, E.; Brouwers, A.H.; van Dam, G.M.; Hoekstra, H.J.
Abstract: Purpose: Sentinel lymph node biopsy (SLNB) has become a widely accepted staging procedure for both breast carcinoma and melanoma. The aim of our study was to systematically review different SLNB techniques and perform a meta-analysis for corresponding identification and false-negative rates. Methods: A systematic review of the literature on SLNB in patients with early stage breast carcinoma and melanoma was performed. Only original study groups were included. The SLN identification rate and false negative rate were pooled for patients with breast carcinoma or melanoma according to radiocolloid tracer, blue dye, indocyanine green (ICG), or a combination of a radiocolloid tracer with blue dye or ICG. Results: Between 1992 and 2012, a total of 154 studies (88 breast carcinoma and 66 melanoma) were reported that met our eligibility criteria. These studies included a total of 44, 172 patients. The pooled SLN identification rate in breast carcinoma and melanoma patients using solely blue dye was 85% (range: 65–100%) and 84% (range: 59–100%), while for radiocolloid alone it was 94% (range: 67–100%) and 99% (range: 83–100%), respectively. Using a combination of radiocolloid and blue, identification rates were 95% (range 94–95%) and 98% (range: 98–98%). Conclusions: The current meta-analysis provides data that favors the use of radiocolloid or radiocolloid combined with a blue dye for SLN identification. Performing SLNB with radiocolloid alone is the technique of choice for experienced surgeons, since blue dye has multiple disadvantages. SLNB using ICG as a fluorescent dye seems a promising technique for the near future.